Conversion of gestational diabetes mellitus to future Type 2 diabetes mellitus and the predictive value of HbA1c in an Indian cohort. Issue 1 (17th March 2016) - Gupta, Y.; Kapoor, D.; Desai, A.; Praveen, D.; Joshi, R.; Rozati, R.; Bhatla, N.; Prabhakaran, D.; Reddy, P.; Patel, A.; Tandon, N.
Abstract: Aim: To investigate the distribution of and risk factors for dysglycaemia (Type 2 diabetes and prediabetes) in women with previous gestational diabetes mellitus in India. Methods: All women ( n = 989) from two obstetric units in New Delhi and Hyderabad with a history of gestational diabetes were invited to participate, of whom 366 (37%) agreed. Sociodemographic, medical and anthropometric data were collected and 75‐g oral glucose tolerance test were carried out. Results: Within 5 years (median 14 months) of the pregnancy in which they were diagnosed with gestational diabetes, 263 (72%) women were dysglycaemic, including 119 (32%) and 144 (40%) with Type 2 diabetes and prediabetes, respectively. A higher BMI [odds ratio 1.16 per 1‐kg/m 2 greater BMI (95% CI 1.10, 1.28)], presence of acanthosis nigricans [odds ratio 3.10, 95% CI (1.64, 5.87)], postpartum screening interval [odds ratio 1.02 per 1 month greater screening interval 95% CI (1.01, 1.04)] and age [odds ratio 1.10 per 1‐year older age 95% CI (1.04, 1.16)] had a higher likelihood of having dysglycaemia. The American Diabetes Association‐recommended threshold HbA1c value of ≥ 48 mmol/mol (6.5%) had a sensitivity and specificity of 81.4 and 90.7%, respectively, for determining the presence of Type 2 diabetes postpartum. Conclusion: The high post‐pregnancy conversion rates of gestational diabetes to diabetes reported in the present study reinforce the need for mandatory postpartum screening and identification of strategies for preventing progression to Type 2 diabetes. Use of the American Diabetes Association‐recommended HbA1c threshold for diabetes may lead to significant under‐diagnosis. What's new?: This study provides new information pertaining to the risk of developing Type 2 diabetes among Indian women with a history of gestational diabetes mellitus. Within 5 years of a gestational diabetes pregnancy, 32% women have progressed to Type 2 diabetes. Another 40% have prediabetes. The prevalence of Type 2 diabetes rose from < 25% within 2 years to almost 50% after 2–4 years' follow‐up. The utility of HbA1c in postpartum screening has been evaluated for the first time from an Indian sample. HbA1c ≥ 48 mmol/mol (6.5%) had a sensitivity and specificity of 81 and 91%, respectively, for determining the presence of Type 2 diabetes postpartum. A detailed analysis of factors associated with increased risk of dysglycaemia is provided.